She wants me, she wants me not: integration of signal detection theory and error management theory to study sexual communication - Brandner, Jordann Leigh (Kansas State University, 2022)
Decades of previous research has found support for a male sexual overperception effect, where men misperceive a woman’s friendliness as sexual interest. This overperception effect is thought to be a leading cause of sexual harassment and assault. However, recent research using Signal Detection Theory failed to find this effect, instead finding that both men and women had high sensitivity when evaluating interest and disinterest. In the present research, videos showing an opposite sex dyad talking were used as stimuli to examine the male sexual overperception effect using Signal Detection Theory. Study 1 (N = 121) attempted to replicate previous research, but failed to replicate sensitivity effects, suggesting that participants were not particularly sensitive or biased in their responses, regardless of sex. Study 2 (N = 124) manipulated the signal-to-noise ratio in an attempt to manipulate bias. Participants who saw more disinterested opposite-sex individuals had a slightly conservative “no”-bias. However, participants who saw more interested opposite-sex individuals did not have a more liberal bias. Study 3 (N = 119) tested competing hypotheses about whether sex ratio manipulations alter bias via signal-to-noise ratio or decision outcomes. Results showed mild support for manipulated sex ratios altering decision outcomes, but only for male participants. Finally, Study 4 (N = 118) tested four interventions that aimed to manipulate bias and/or sensitivity. The pre-/posttest biases and sensitivities were not significantly different depending on the manipulation condition, however results did trend in the hypothesized directions. Across the studies, Mate Value, Short-Term Mating Orientation, Long-Term Mating Orientation, Life History Strategy, and Sexual Aggression showed minimal effects on sensitivity or bias. Additionally, across the studies, the traditional male sexual overperception bias was not found, suggesting that the male sexual overperception effect could be mitigated by recent cultural pressures or previous analytical methods could be flawed.
Keywords: Signal detection theory; Error management theory; Sexual overperception